Domestic banks as lightning rods? Home bias during the Eurozone crisis - Orkun Saka (London School of Economics and Political Science (LSE), European Institute, 2017)
Governments and domestic banks in Europe have attracted criticism due to the heightening inclination of banks to hold more local sovereign debt in the midst of the crisis. This has traditionally been interpreted as an evidence of financial repression or moral suasion. By using a novel dataset on bank-level exposures to sovereign and private debt covering the entire Eurozone crisis, I confirm that sovereign debt has been reallocated from foreign to domestic banks at the peak of the crisis. Furthermore, this reallocation has been especially visible for banks as opposed to other domestic private agents and cannot be explained by the risk-shifting tendency of the banks located in troubled countries. However, in contrast to the previous literature focusing only on sovereign debt, I show that banks' private sector exposures have suffered (at least) equally from a rising home bias. Finally, I present a direct information channel and demonstrate that foreign banks – free from moral suasion – located in informationally closer territories have relatively increased their exposures to crisis-countries.
Keywords: F21; F34; F36; G01; G11; G21; 330; Home bias; Information asymmetries; Eurozone crisis; Sovereign debt